Frontispiece: Dibenzo[a, e]pentalenophanes: Bending a Non‐Alternant Hydrocarbon. Issue 29 (23rd May 2018) - Hermann, Mathias; Wassy, Daniel; Kratzert, Daniel; Esser, Birgit
Abstract : Dibenzo[ a, e ]pentalene was brought into a bent shape by incorporation into cyclophane structures. Burgess' reagent accomplished the last, strain‐inducing dehydration reaction, powerful enough to compensate for the antiaromatic character built‐up in the central pentalene unit. The bend angles of the dibenzopentalene unit had values of up to 88°, spanning a near semi‐circle. For more details, see the Full Paper by B. Esser et al. on page 7374 ff.